Mucoadhesive drug delivery systems - Siafaka, Panoraia I. (Henry Stewart Talks, 2022)
Introduction to mucoadhesive drug delivery systems, History of mucoadhesive systems, Definition of mucoadhesion, Theories of mucoadhesion, Advantages and disadvantages of mucoadhesive systems, Bioadhesive polymers, Dosage forms as MDDS, Advanced mucoadhesive nanosystems